Receipt from the Pasteur Institute to the community of Éply, France - Institut Pasteur (Paris, France) (1887)
The community of Éply in France raised 20 francs "to found an establishment for the treatment of hydrophobia." In this context, hydrophobia is an irrational fear of water brought on as a symptom of rabies. Receipt contains postage stamp.
Keywords: Rabies--Treatment; Rabies; Éply, France; Institut Pasteur (Paris, France)